Midterm Outcomes of Talocalcaneal Coalition Arthroscopic Resection in Adults. (August 2022) - Wang, Anhong; Chen, Linxin; Pi, Yanbin; Zhao, Feng; Xie, Xing; Jiao, Chen; Hu, Yuelin; Jiang, Dong; Guo, Qinwei
Background: Arthroscopic resection of the talocalcaneal coalition (TCC) has been reported to be associated with good short-term outcomes. However, the midterm outcomes of this approach remain uncertain. Methods: We performed a retrospective study of patients who underwent arthroscopic resection for symptomatic TCC. The patients were divided into 2 groups (group P, patients with isolated posterior facet coalition; and group MP, patients with both middle and posterior facet coalition). The preoperative and postoperative visual analog scale (VAS) scores for pain and American Orthopaedic Foot & Ankle Society (AOFAS) scale scores were calculated. The postoperative AOFAS and VAS scores between the 2 groups were analyzed. Patient satisfaction was also assessed. Results: Thirty-two patients were included in this study. The mean age at the time of surgery was 26.0±8.5 years, and the mean follow-up period was 56.9±18.0 months. Thirteen (41%) patients were in group P, whereas 19 (59%) patients were in group MP. Postoperative VAS and AOFAS scores improved more significantly than preoperative scores. At the final follow-up, excellent and good subjective outcomes were attained in 26 patients (81%), fair and poor outcomes in 6 patients (19%). There were no statistical differences in the postoperative AOFAS (91.0±7.0 vs 85.8±10.8, P = .532) and VAS score (2.1±1.7 vs 4.0±2.6, P = .537) between patients with the ratio of coalition/posterior facet more than or less than 50%. There were no statistical differences in postoperative VAS score (1.8±1.3 vs 2.6±2.2, P = .236) and AOFAS score (92.5±5.6 vs 89.2±8.7, P = .297) between group P (n=13) and group MP (n=19), either. Three patients (9.4%) had complications, including these notable findings: 1 patient complained of restricted dorsal flexion, 1 with computed tomography–proven coalition recurrence, and 1 with partial tibial nerve injury. Conclusion: We found that TCC arthroscopic resection was generally associated with reasonable outcomes at midterm follow-up. Level of Evidence: Level IV, case series.